The Incidence, Risk Factors, and Complications Associated With Surgical Delay in Multilevel Fusion for Adult Spinal Deformity. Issue 3 (April 2022) - Wade, Sean M.; Fredericks, Donald R.; Elsenbeck, Michael J.; Morrissey, Patrick B.; Sebastian, Arjun S.; Kaye, I. David; Butler, Joseph S.; Wagner, Scott C.
Study Design: Retrospective database review. Objectives: The incidence and risk factors for surgical delay of multilevel spine fusion for adult spinal deformity (ASD), and the complications corresponding therewith, remain unknown. The objectives of this study are to assess the incidence and risk factors for unexpected delay of elective multilevel spinal fusions on the date of surgery as well as the postoperative complications associated with these delays. Methods: We conducted a retrospective review of the ACS-NSQIP database on patients undergoing elective spinal instrumentation of greater than 7 levels for ASD between the years 2005 and 2015. Preoperative risk factors for delay and postoperative complications were compared between the cohorts of patients with and without surgical delays. Results: Multivariate analysis of 1570 (15.6%) patients identified advanced age, male sex, American Society of Anesthesiologists (ASA) Class 4, and history of smoking as independent risk factors for delay. Patients experiencing surgical delay demonstrated longer operative times, increased intraoperative bleeding, longer hospitalizations, and significantly higher rates of postoperative complications. Patients experiencing delay demonstrated an almost 7-fold increase in mortality rate (3.4% vs 0.5%, P < .001). Conclusions: Delays in elective surgical care for spinal deformity are negatively related to patient outcomes. Advanced age, male sex, increased ASA class, and a history of smoking cigarettes place patients at risk for surgical delay of multilevel spinal fusion. Patients experiencing surgical delay are at higher risk for postoperative complications, including a 7-fold increase in mortality. These findings suggest that ASD surgery should be postponed in patients experiencing a delay, until modifiable risk factors can be medically optimized, and perhaps postponed indefinitely in those with nonmodifiable risk factors.